Turnover of Phosphatidic Acid through Distinct Signaling Pathways Affects Multiple Aspects of Pollen Tube Growth in Tobacco - Pleskot, Roman; Pejchar, Přemysl; Bezvoda, Radek; Lichtscheidl, Irene K.; Wolters-Arts, Mieke; Marc, Jan; Žárský, Viktor; Potocký, Martin (Frontiers in Plant Science, 2012)
Phosphatidic acid (PA) is a substantial intermediate in membrane lipid metabolism and also acts as an important component of the signalling pathways, regulating the spatio-temporal dynamics of the endomembrane system and cytoskeleton. Using tobacco pollen tubes as a model, we addressed signalling properties of PA in the single plant cell probing functions of three most relevant enzyme activities regulating production/localization and degradatin of PA – phospholipases D (PLD), diacylglycerol kinases (DGK) and lipid phosphate phosphatases (LPP). Phylogenetic analysis indicated a very dynamic evolution of all these three PA-modifying enzymes in land plants with many clade-specific duplications or losses. An in silico transcriptomic survey suggested enhanced recruitment of all three PA regulating activities into the pollen development – trend, surprisingly the most apparent in the case of DGKs. Using established specific inhibitors we could distinguish the contributions of PLDs, DGKs and LPPs into the PA regulated processes. LPPs inhibitors corroborated our previous data implying enhanced PA in the enhanced pollen tube growth – all LPPs inhibitors tested significantly stimulated pollen tube growth. The same effect was achieved by suppression of LPPs expression using antisense knock-down. In contrast, reduction of PA levels compromised membrane trafficking and pollen tube growth but not early endocytosis. Also the tip localised deposition of cell wall material (especially pectins) was disrupted after the inhibition of PA-producing enzymes. In contrast to PLD inhibition, DGK inhibition induced intracellular accumulation of pectins. While inhibition of DGK-produced PA changed vacuolar dynamics and morphology of pollen tubes, actin polymerization was positively regulated by PLD-derived PA. Our results clearly demonstrate strikingly different roles of PA produced by PLDs and DGKs in pollen tube growth.